Theoretical Model of Critical issues in Informed Consent in HIV Vaccine Trials - Lewis, Cindi A. (2014)
The informed consent (IC) process for HIV vaccine trials poses unique challenges and would benefit from improvements to its historically-based structure and format. Here, we propose a theoretical framework that provides a basis for systematically evaluating and addressing these challenges. The proposed framework follows a linear pathway, starting with the precondition of voluntariness, three main variables of valid decision-making (competency, provision of information and understanding) and then the consequential outcome of either refusal or consent to participate. The existing literature reveals that culturally appropriate provision of information and resultant understanding by the vaccine trial participant are among the most significant factors influencing the authenticity of valid decision-making, though they may be overridden by other considerations, such as individual altruism, mistrust and HIV-related stigma. Community collaborations to foster bidirectional transmission of information and more culturally tailored consenting materials therefore represent a key opportunity to enhance the informed consent process. By providing a visual synopsis of the issues most critical to IC effectiveness in a categorical and relational manner, the framework provided here presents HIV vaccine researchers a tool by which the informed consent process can be more systematically evaluated and consequently improved.